(untitled) (Medico Legal Update, 2021)
Stress is a state created by amendment in atmosphere that is damaging to the person’s equilibrium and is mostly prevalent in nursing students. The study aims to measure the stress level of nursing students. Sample size consisted of 63 nursing students of GNM 1st year and B.Sc.(N) Post basic 1st year chosen by convenience non-probability sampling technique and informed consent were taken from subjects. The UN Management stress tool was used to collect data which was taken from UNO Management Booklet of series. The results of the study has revealed that 97% of GNM 1st year students and 67% of Post Basic B.Sc. Nursing students were in moderate stress. The stress level is high in GNM 1st year students as compare to post basic BSc Nursing 1st year. Mean stress score of Post Basic B.Sc.(N) 1st year and GNM 1st year was 17 ± 2.3 & 23 ± 3.5.